2012
DOI: 10.1111/j.1464-410x.2012.11466.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evidence suggests repeated intravesical application of botulinum toxin A injections may improve treatment efficacy of interstitial cystitis/bladder pain syndrome

Abstract: What's known on the subject? and What does the study add? A single set of botulinum toxin A (BoNT‐A) injections relieves clinical symptoms of interstitial cystitis/bladder pain syndrome (IC/BPS), but lacks long‐term effect. An inadequate anti‐inflammatory effect is likely to cause treatment failure. The study shows that chronic inflammation and apoptotic signalling molecules are significantly reduced after repeated intravesical BoNT‐A injection in patients with IC/BPS. It also shows that repeated BoNT‐A injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 26 publications
0
64
0
Order By: Relevance
“…44 Shie et al injected 100 U in the posterior and lateral bladder walls with re-treatment every six months regardless of symptom status for a total of four treatments. 46 After treatment one but not treatments two through four, hydrodistension was performed. Patients were followed for two years with improvements in pain VAS, O'Leary-Sant scores and frequency restored with each treatment.…”
Section: Aua Guideline Amendmentmentioning
confidence: 99%
“…44 Shie et al injected 100 U in the posterior and lateral bladder walls with re-treatment every six months regardless of symptom status for a total of four treatments. 46 After treatment one but not treatments two through four, hydrodistension was performed. Patients were followed for two years with improvements in pain VAS, O'Leary-Sant scores and frequency restored with each treatment.…”
Section: Aua Guideline Amendmentmentioning
confidence: 99%
“…[184][185][186][187] The duration (approximately 9-10 months) 186 and strength of response seem to be maintained with repeat injections and rate of adverse events low.…”
Section: Botulinum Toxin a (Btx-a) (Option Grade C)mentioning
confidence: 99%
“…5 Previous study demonstrated the degree of glomerulations decreases after repeated onabotulinumtoxinA injection. 17 Although the actual mechanism for this onabotulinumtoxinA effect on angiogenesis is unknown, it is important to elucidate which signal molecules are responsible for the regulation of angiogenesis after onabotulinumtoxinA treatment. The glomerulations and vascular permeability of IC/BPS bladder tissues seem to be because of inflammatory stimulation.…”
Section: Commentmentioning
confidence: 99%